The Basic Concepts of Modelling Railway Track Systems Using Conventional and Finite Element Methods - Puguh Budi Prakoso (Universitas Lambung Mangkurat, 2012)
- The classical concepts of railway track analysis, such Beam on Elastic Foundation (BOEF), Winkler’s theory or Zimmermann method are categorized as one-dimensional analysis of a railway structure and are simplification of a beam laid on a continuous support (soil’s subgrade or foundation). These methods are still very useful for analyzing a simple design and analysis of railway track systems. Unfortunately, for doing a complex analysis of a railway track, these methods have lack of capabilities, since they only take into account one-dimensional system and neglect the actual discrete support provided by crossed sleeper, ballast, sub ballast mat and subgrade.Nowadays, the use of computer software for doing Finite Element Method (FEM) or Finite Element Analysis (FEA) of a structure is very common for engineers. FEA consists of a huge amount of complex calculations; therefore, a manual calculation by hand is almost impossible to be done. Hence, the use of computer software will be very useful in this manner. The applications of FEM using software also widen in the field of railway infrastructure design and analysis. There are many advantages of using FEM method using computer. However, related to its complexities, one should understands the concepts and “knows-how” to solve the problems, to idealize the structure into FEM model in computer, and to choose the suitable elements and its behaviours, and also the correct method.Thispaper is presented to discuss the basic theories behind the conventional and advanced ways of modelling of railway track system, to show the basic concepts of modelling railway track systems using FEM, to present two- and three-dimensional FEM models of railway superstructures which are built using software ANSYS, and to demonstrate the way of doing the verification of the results using Zimmermann method.